Proportional representation and its effects on South African democratic accountability: a case study of South African local government - Perkins, Brendan (My University, 2023)
Despite South Africa having six elections since the end of Apartheid, amounting to a period of nearly 30 years, the electoral system in the Republic is yet to be entrenched. The established electoral arrangement of proportional representation (PR) has never been constitutionally codified, a factor contributing to the almost continuous debate on its merits within Democratic South Africa. Over these past decades, electoral commissions have been established to judge the current system: specifically on the principles of fairness, inclusiveness, simplicity, and accountability. It is this last value of accountability, especially democratic accountability, that has been at the forefront of the discussion on the merits of South Africa’s electoral system. This research paper, like many studies before it, is concerned with the purported advantages and disadvantages of the current PR system, and how it either benefits or hinders accountability to the electorate. However, what differentiates this study, is its additional analysis of the electoral system found at the South African local governmental level, which harbours a mixed member system, that is somewhat similar to the proposed alternative for a new national system. Nevertheless, this paper in its analysis found little evidence that the mixed member system at the local level manages to merge the democratic virtues of greater accountability to a constituency with the fairness of PR. Instead, it was hampered by unresponsive ward councillors, apathetic municipal councils, and general party interference. However, the research did find potential areas for reform at the local level: to help better differentiate its two types of elected representatives, and to make them more responsive to local forces, thus more accountable. If a national mixed-member system is to be implemented, these concerns should be noted. This paper utilised a mixed-methods approach in conducting this research, as well as employing a theory-testing case study analysis of local government.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts in Political Studies to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2023
Keywords: Electoral Systems; Proportional Representation; Democratic Accountability